Modeling and querying facts with period timestamps in data warehouses - Mahlknecht, Giovanni; Dignös, Anton; Kozmina, Natalija (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, we study various ways of representing and querying fact data that are time-stamped with a time period in a data warehouse. The main focus is on how to represent the time periods that are associated with the facts in order to support convenient and efficient aggregations over time.
Keywords: data warehouses; time periods; logical models